Improving Of IS-CFAR Using Wavelet De-Noising For Smoothing The Noise In Reference Cells - Jameel Hadi, Hadi; Khalid Abed Ali, Waleed (Journal of Engineering and Sustainable Development, 2014)
Constant false alarm rate (CFAR) algorithms allow RADAR systems to set detection thresholds and isolated the target from noise or clutter to keeping the false alarm rate at certain level. In this paper a technique added to Improved Switching IS-CFAR system is used to reduce the non-homogenous effect and clutter wall, this technique is called wavelet de-noising. The detection performance of Improving IS-CFAR using wavelet de-noising (I2S-CFAR) processor is compared with the IS-CFAR detectors for homogeneous, non-homogenous and clutter wall. By using wavelet de-noising a gain in signal to noise ratio (SNR) about 2.6dB achieved for the same probability of detection.